1999
DOI: 10.1124/mol.55.6.1077
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recognition of Vitamin D Receptor Conformations Mediates Promoter Selectivity of Vitamin D Analogs

Abstract: The transcription factor VDR is the nuclear receptor for 1alpha, 25-dihydroxyvitamin D3 (VD) and the mediator of all genomic actions of the nuclear hormone and its synthetic analogs. The sharp biological profile of the model VD analog 1(S), 3(R)-dihydroxy-20(R)-(5'-ethyl-5'-hydroxy-hepta-1'(E), 3'(E)-dien-1'-yl)-9,10-secopregna-5(Z),7(E),10(19)-triene (EB1089) (i.e., its high antiproliferative effect combined with low calcemic actions) has been correlated with the selectivity of EB1089 to activate heterodimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…The impact of an additional conformation c2 of the PPAR␥ and CAR LBD has not yet been investigated in detail, but in the case of VDR the conformation c3 represents a silent, nonagonistic state of the LBD (49). With VDR both conformations were only stabilized in the presence of agonist as reported previously (48,50), whereas with PPAR␥ at least a clearly weaker amount as in the presence of specific ligand was found. However, in the case of CAR the addition of ligand showed no significant effect on the stabilization of c1.…”
Section: Coa Interaction Of the Unliganded And Liganded Ppar␥-mentioning
confidence: 57%
“…The impact of an additional conformation c2 of the PPAR␥ and CAR LBD has not yet been investigated in detail, but in the case of VDR the conformation c3 represents a silent, nonagonistic state of the LBD (49). With VDR both conformations were only stabilized in the presence of agonist as reported previously (48,50), whereas with PPAR␥ at least a clearly weaker amount as in the presence of specific ligand was found. However, in the case of CAR the addition of ligand showed no significant effect on the stabilization of c1.…”
Section: Coa Interaction Of the Unliganded And Liganded Ppar␥-mentioning
confidence: 57%
“…*P50.05 cancer and PC-3 and DU-145 cells display many alterations that are associated with metastatic androgen-independent cancer, including aberrant p53 function and dysregulation of normal apoptotic responses (Carrol et al, 1993;Ewing et al, 1995;Isaacs et al, 1994;Tamimi et al, 1996;Mackey et al, 1998) and furthermore do not readily undergo apotosis when exposed to 1a,25(OH) 2 D 3 Zhuang and Burnstein, 1998). Interestingly, Carlberg and co-workers have demonstrated that either di erent VDR co-repressors complexes or structurally di erent vitamin D 3 analogs demonstrate VDRE selectivity (Quack and Carlberg, 1999;Nayeri and Carlberg, 1997;Danielsson et al, 1997;Polly et al, 2000). These ®ndings would allow for di erential regulation of genes by 1a,25(OH) 2 D 3 , within the same cell line, and disruption of a speci®c co-factor, such as a co-repressor with associated HDAC activity, would consequently silence a speci®c subset of 1a,25(OH) 2 D 3 -responsive genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that a specific subset of VDRE (IP9) are more commonly associated with genes that mediate growth arrest and apoptosis (Danielsson et al, 1997;Quack and Carlberg, 1999). Furthermore, IP-9-type response elements have been shown to associate with the corepressors NCoR1 or SMRT (Polly et al, 2000).…”
Section: Discussionmentioning
confidence: 99%